Perceptions of Medical Sciences Students Towards Probiotics - Mohamad Asghari Jafar Abadi; Reza Mahdavi; Zeinab Nikniaz; Laleh Payahoo (Tabriz University of Medical Sciences, 2012)
Background: Regarding the importance of probiotics in prevention of different diseases, the knowledge ofpeople particularly health-related professionals about the beneficial effects and availability of probiotic productsis important. Considering the limited studies, the present study was conducted to assess the knowledge ofmedical sciences students as future provider of health information about probiotics in Tabriz, Iran.Methods: This cross-sectional study was carried out on 296 medical sciences students from different facultymajors with mean age of 22 ± 4 years. The students completed two self-administered questionnaires; the onewas about the demographic characteristics and the other one with nine closed questions as for knowledge aswell as probiotics and their health effects and 2 questions related to availability of probiotic products. Scoringof 9 knowledge questions was divided to three sections 0-3, 4-6, 7-9 and classified as poor, acceptable andgood, respectively. The Chi-square test was used to examine the differences in knowledge of the studentsacross different gender, major and degree groups.Results: Six percent of students had poor, 43% acceptable, and 51% good knowledge. Total mean±(SD) ofknowledge was 6.25 ±1.6 . Answers of students about the availability of probiotic products were 36.9% low,48.1% moderate, and 15% high. Comparison of knowledge result between different major and degree groupswas statistically significant (P<0.05).Conclusion: Although students had approximately acceptable level of knowledge about probiotics and theirhealth effects, their awareness about common available form of probiotic products was low. The use ofefficient co-educational materials such as teaching new findings for students may be beneficial.